Cardiac Tamponade: A Rare Manifestation of Familial Mediterranean Fever - Malek, Abdolreza; Zeraati, Tina; Sadr-Nabavi, Ariane; Vakili, Niloofar; Abbaszadegan, Mohammad Reza (Case Reports in Rheumatology, 2022)
Familial Mediterranean fever (FMF) typically presents with recurrent attacks of fever and serosal inflammation with peritoneum, pleura, and synovium. We usually do not expect pericardial involvement at the early stages. FMF is an autoinflammatory disease, usually inherited with an autosomal recessive pattern. The patients typically have biallelic mutations in the MEFV gene, located on chromosome 16. Colchicine is the first-line treatment of FMF, which not only plays a crucial prophylactic role regarding the attack episodes, but also prevents amyloidosis. Colchicine resistance and intolerance in FMF patients have been rarely reported. Alternative anti-inflammatory agents are understood to be helpful in such cases. We describe a 13-year-old boy referred to our pediatric department complaining of chest pain, dyspnea, and tachycardia. Due to the massive pericardial and pleural effusion, a pericardiocentesis was performed, and a chest tube was inserted. Cardiac tamponade was considered as the initial diagnosis. After a month, he faced another episode of pleuritic chest pain, fever, tachycardia, and pleural and pericardial effusion. Evaluation for probable differential diagnoses including infection, malignancy, and collagen vascular disease showed no remarkable results. Finally, the mutation found by whole exome sequencing was confirmed by direct Sanger sequencing revealing a heterozygote c.44G > C (p.Glu148Gln) mutation in exon 2, confirming the clinical diagnosis of familial Mediterranean fever. Since he seemed to be nonresponsive to the maximum standard dose of colchicine, 100 mg of daily dapsone was added to his treatment regimen, which controlled the attack episodes well. FMF, while rarely initiated with cardiac manifestation, should be considered in patients with any early signs and symptoms of cardiovascular involvement.